Biological reduction of aflatoxin B1 in yogurt by probiotic strains of Lactobacillus acidophilus and Lactobacillus rhamnosus - Mosallaie, Fatemeh (Food Sci Biotechnol, 2019)
The present study was conducted to investigate the ability of two probiotic strains, L. acidophilus PTCC 1643 and L. rhamnosus PTCC 1637, to bind aflatoxin B(1) (AFB(1), 20 ng/ml) in comparison with yogurt starter cultures, at equal bacterial count (~ 10(9) LogCFU/ml) during a 21-day storage period at 4 °C. All assessed treatments exhibited high percentages of AFB(1)-binding, ranged from 64.56 to 96.58%. However, the ability of probiotic bacteria was statistically higher than yogurt starter cultures. Aflatoxin binding ability of the selected lactic acid bacteria was dependent on both time and bacteria species. The highest and the lowest percentages of AFB(1-)removal was observed at 11th day of cold storage by L. rhamnosus (96.58 ± 3.97%) and at the first day of storage for yogurt starter cultures (64.56 ± 5.32%), respectively. The stability of bacterial cells-AFB(1) complex was remarkable, since only 0.84–26.75% of bounded AFB(1) was released from bacterial cells after 3 times washing during the storage period.